2010
DOI: 10.1111/j.1467-8624.2010.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience‐Based and On‐Line Categorization of Objects in Early Infancy

Abstract: What processes do infants employ in categorizing? Infants might categorize on line as they encounter category-related entities; alternatively, infants might depend on prior experience with entities in formulating categories. These alternatives were tested in forty-four 5-month-olds. Infants who were familiarized in the laboratory with a category of never-before-seen objects subsequently treated novel objects of the same category as familiar --they categorized on line --just as did infants who were exposed to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
54
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 94 publications
3
54
1
1
Order By: Relevance
“…As there are no “warm up”, “training”, or “learning” as there might be in a habituation or familiarization phase, infants use their existing knowledge of category membership (or not) to guide their interactions with these objects. The influence of prior knowledge on a categorization task has been documented in infants much younger than the 18-month-olds studied here: Bornstein and Mash (2010) found that 5-month-olds who were exposed to a category of novel objects for two months at home showed robust categorization in a laboratory task at the outset (i.e., in the absence of a familiarization or habituation phase).…”
Section: Discussionmentioning
confidence: 71%
“…As there are no “warm up”, “training”, or “learning” as there might be in a habituation or familiarization phase, infants use their existing knowledge of category membership (or not) to guide their interactions with these objects. The influence of prior knowledge on a categorization task has been documented in infants much younger than the 18-month-olds studied here: Bornstein and Mash (2010) found that 5-month-olds who were exposed to a category of novel objects for two months at home showed robust categorization in a laboratory task at the outset (i.e., in the absence of a familiarization or habituation phase).…”
Section: Discussionmentioning
confidence: 71%
“…Specifically, the use of such novel stimuli can help ensure observed effects are due to the experimental manipulation and not a priori knowledge (see also, Ard & Beverly, 2004;Bornstein & Mash, 2010). In the real world, particularly for children, all objects were once novel, unnamed objects (Horst, 2013;Horst, McMurray, & Samuelson, 2006)-only through cumulative, gradual learning do we learn to attribute identities to the objects around us.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given that faces are extremely common in infants’ everyday experience, it would not be surprising if more casual daily encounters with objects other than faces would not have the same effect on infants’ learning. Remarkably, however, Bornstein and Mash (2010) found that infants’ attention to completely novel objects in a laboratory task was influenced by a few minutes of daily exposure to pictures of those objects over a period of a few weeks. And, Kovack-Lesh et al (2008; 2012) found a connection between exposure to pets at home and 4-month-old infants memory for and categorization of images of cats in the laboratory.…”
mentioning
confidence: 93%
“…A critical question is how much such responding reflects on-line processing versus existing knowledge (Bornstein & Mash, 2010; Haith, 1998; Madole & Oakes, 1999; Mandler, 1999). Clearly, responding to abstract or novel objects and pictures (Younger, 1985; Younger & Cohen, 1986) reflects knowledge infants acquired in the task.…”
mentioning
confidence: 99%